Financing innovative SMES in Kenya - Kainda Gitonga (My University, 2015)
Innovative small medium enterprises (SMEs) are considered to be of strategic importance in research and innovation either through the creation -and adoption of new technologies, ideas or new business models. These firms are considered to be very critical to an economy as they provide rapid growth and are significant contributors to the overall growth. The literature reviewed showed that despite their significance, ISMEs face considerable constraints, both from the supply and demand sides; in obtaining external finance to sustain their growth as a result of the high degree of uncertainty associated with young companies . In addition, the complex nature of the innovation process that requires continuous and in multiple rounds of finance during the innovation cycle makes access to capital even more tenuous, The purpose of the study was to determine how ISMEs can overcome these constraints and the factors that contribute towards the success of these firms in obtaining funding. The research methodology adopted was a case study on Amandari Limited, a- firm in the early stage of development that sought and obtained external financing to implement its innovative idea. Data collection was ,by way of in-depth interviews conducted on key participants including the entrepreneur, her advisors and investors (including those who did not invest). The findings indicate that the key success factors include the ability of the entrepreneur to structure and present the innovative idea in a manner that demonstrates the value of the idea and the firm's future profitability. For firms in the early stage, investors invest in the entrepreneur and on the basis of the relationship that they have with the entrepreneur. Therefore the entrepreneur's ability to leverage on his/her social and business networks to increase the pool of investors is also a key factor . Last but not least, the ability of the company to demonstrate reduction of the informational asymmetries In the business is also critical.
Dissertation submitted to Strathmore Business School, Strathmore University, in partial fulfillment of the requirements for the degree of Masters in Business Administration